2018
DOI: 10.1111/1365-2435.13206
|View full text |Cite
|
Sign up to set email alerts
|

Edaphic factors, successional status and functional traits drive habitat associations of trees in naturally regenerating tropical dry forests

Abstract: Many studies have examined individual environmental drivers of tropical tree species distributions, but edaphic and successional gradients have not been considered simultaneously. Furthermore, determining how functional traits influence species distributions along these gradients may help to elucidate mechanisms behind community assembly. To assess the influence of environmental filtering on tropical dry forest (TDF) tree species distributions, we used forest inventory data from sites with large edaphic and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 50 publications
0
31
0
3
Order By: Relevance
“…One reason is that nutrient strategies vary widely among tropical plant species, but are only studied for a small proportion of diverse tropical plant communities (van Breugel et al, ; Dalling, Heineman, Lopez, Wright, & Turner, ; Nasto et al, ), and usually not concurrently with species successional strategies (but see Craven, Hall, Berlyn, Ashton, & Breugel, ). This is only the second study that quantitatively assessed how soil nutrients and successional age simultaneously affect the abundance of plant species across secondary forests in a tropical landscape (Werden et al, ). Our data can be used to select species with contrasting successional and soil resource associations for more detailed explorations of their nutrient strategies and associated traits and experimental studies on the mechanisms governing soil resource partitioning (Batterman et al, ; Palmiotto et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason is that nutrient strategies vary widely among tropical plant species, but are only studied for a small proportion of diverse tropical plant communities (van Breugel et al, ; Dalling, Heineman, Lopez, Wright, & Turner, ; Nasto et al, ), and usually not concurrently with species successional strategies (but see Craven, Hall, Berlyn, Ashton, & Breugel, ). This is only the second study that quantitatively assessed how soil nutrients and successional age simultaneously affect the abundance of plant species across secondary forests in a tropical landscape (Werden et al, ). Our data can be used to select species with contrasting successional and soil resource associations for more detailed explorations of their nutrient strategies and associated traits and experimental studies on the mechanisms governing soil resource partitioning (Batterman et al, ; Palmiotto et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, both have been poorly studied in the context of forest succession (Arroyo‐Rodríguez et al, ; Kraft & Ackerly, ; Leibold et al, ; Meiners, Cadotte, Fridley, Pickett, & Walker, ). Here, we presented, to our knowledge, the first quantitative assessment of the relative contributions of these two ecological processes to the variation in the species composition of tropical secondary forests at different spatial scales (but see Jakovac et al, ; Lawrence, ; Werden et al, ). Our results corroborate evidence from other plant communities (Myers & Harms, ), including temperate successional forests (Verheyen & Hermy, ) that the successional niche, dispersal limitation and local edaphic heterogeneity concurrently structure early successional plant communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In young secondary forests, soil fertility in terms of N and P can have significant effects on plant performance (Ayala‐Orozco et al, ; van Breugel et al, ; Lawrence, ; Powers & Marín‐Spiotta, ). For example, Werden et al () found that soil chemistry, including P, determined the distribution of 82 species across 84 successional dry forest plots in Costa Rica. Likewise, Davidson et al () showed that experimental addition of N significantly increased tree biomass in a young successional moist forests in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Lu, Moran, and Mausel () showed that higher available N concentrations on Alfisols positively affected forest biomass accumulation in early successional forests in Brazil, but that this effect was not present on Oxisols and Ultisols. In successional dry forests in Costa Rica, variation in soil chemistry and texture explained a substantial portion of species’ occurrences and distribution (Powers, Becknell, Irving, & Pèrez‐Aviles, ; Werden, Becknell, & Powers, ), but the relationship between soil properties and above‐ground biomass was weak (Becknell & Powers, ). At a regional scale, above‐ground biomass of secondary forests across the Neotropics does not seem to be related to soil cation exchange capacity (Poorter et al, ).…”
Section: Introductionmentioning
confidence: 99%